Challenges and Opportunities in the Practice of Environmental Education in the Amazon Context: a Legal-Constitutional Approach - Ferreira Junior, Edinaldo Inocêncio (Revista Nacional de Gerenciamento de Cidades, 2023)
This work aims to analyze the challenges and opportunities encountered in the practice of environmental education in the Amazonian context, adopting a legal-constitutional approach. The methodology used consists of a literature review and critical analysis of studies, laws, and legal documents related to environmental education and environmental protection in the Amazon region. The originality and relevance of this study lie in filling a theoretical gap by investigating how the legal-constitutional approach can contribute to the effectiveness of environmental education in the Amazon. Furthermore, the addressed theme holds great academic and social significance, considering the importance of the Amazon region for global biodiversity and the fundamental role of environmental education in awareness and environmental preservation. The main results indicate the need for greater integration between legal-constitutional aspects and the practice of environmental education in the Amazon region. The legal approach contributes to strengthening legal instruments for environmental protection and promoting greater awareness and engagement of society in preserving the Amazon. The theoretical and methodological contributions of this study are related to understanding the importance of the legal-constitutional framework as a fundamental support for the effectiveness of environmental education. Additionally, the social and environmental implications are significant, as effective environmental education can promote public awareness and encourage sustainable practices, thereby contributing to the preservation of the environment and sustainable development of the Amazon region.